Geographic spread of epidemic multiresistant Staphylococcus aureus clone in Brazil. - Teixeira, L A (1995)
Staphylococcus aureus isolates from five large teaching hospitals and one medium-size community hospital located in geographically distant parts of Brazil, in the south and southeast (Rio de Janeiro, Niteroi, Sao Paulo, Porto Alegre) and in the north (Manaus), were tested for their antibiotic resistance patterns and genetic backgrounds. Eighty-five of the 152 isolates were identified as methicillin-resistant S. aureus (MRSA) by using a combination of an agar dilution screen and a mecA gene-specific DNA probe. All MRSA isolates were resistant to penicillin, erythromycin, gentamicin, oxacillin, and cephalothin, and the majority of isolates (74%) were also resistant to chloramphenicol, sulfamethoxazole-trimethoprim, ciprofloxacin, and clindamycin as well and were susceptible only to vancomycin. Isolates obtained from hospitals in Sao Paulo, Rio de Janeiro, Niteroi, and Porto Alegre (1,600 km from one another) and Manaus (3,700 km from Rio de Janeiro) were examined by a variety of molecular fingerprinting techniques: the nature of the mecA polymorph and Tn554 attachment sites and restriction fragment length polymorphism of genomic DNAs after SmaI restriction and separation of the digested DNA by pulsed-field gel electrophoresis. The overwhelming majority of the isolates shared a common pulsed-field gel electrophoresis pattern and carried mecA polymorph III in combination with Tn554 pattern B, indicating the presence of a single, epidemic MRSA clone spread over large geographic distances of Brazil.